RUMOR RESILIENCE: HOW BUSINESSES ECONOMICALLY RESPOND TO STOCHASTIC RUMOR SPREAD - Zhang, Hongzhi; Wu, Bo (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article investigates the economic impact of stochastic rumor propagation on businesses in the digital age. Drawing from interdisciplinary literature, it examines decision-making under uncertainty, digital media's role in rumor spread, and strategic responses. The findings highlight the need for businesses to develop resilience and agility in navigating rumor-induced challenges.